Construction and Evaluation of a Uniaxial Mechanical Actuated Vibration Shaker - Lafta, Hameed D.; Murad, Nasrat K.; Khamas, Ihasan J.; Abdalla, Tebin F. (Al-Khwarizmi Engineering Journal, 2018)
In the present paper a low cost mechanical vibration shaker of rotating unbalanced type with uniaxial shaking table was designed and constructed in an attempt to provide opportunities for experimental testing and application of vibration in experimental modal analysis, stress relief of weldments, effect of vibration on heat transfer and seismic testing of civil engineering structures. Also, it provides unexpressive solution to enhance the knowledge and technical skills of students in mechanical vibration laboratory. The shaker consists of a five main parts shaker frame, shaker table, flexible support, drive motor, and eccentricity mechanism. The experimental results show that the amplitude of the shaker is increased with increasing the frequency ratio and the maximum value was attained near the resonance condition.  Also, the magnitude of amplitude is increased with increasing the eccentric mass and eccentricity values. A reasonable agreement with theoretical results shows that the shaker can be used with reliable results in vibration testing purposes. Also, in this paper, the frequency ranges of the shaker were determined for constant displacement and for constant acceleration tests to satisfy all the frequency limitation requirements of the mechanical shaker.